2014
DOI: 10.1002/adom.201300380
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Photodeposition of Ag on Ferroelectric Surfaces with Below‐Bandgap Excitation

Abstract: Ferroelectric lithography, a recent method of fabricating functional interfaces, traditionally involves photoreduction on polarized ferroelectric surfaces at optical energies above the bandgap of the ferroelectric. In this work, for the first time, photochemical deposition of elemental Ag nanoparticles on a specifically poled lithium niobate substrate is reported, with a broad white‐light spectrum transmitted through the crystal. The transmitted light has energies only below the bandgap, leading to the conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Given also that charge transfer from LN to Ag or 4ABT is permitted under UV irradiation, this raises the question as to why sustained PIERS is observed on x -cut LNOI–Ag–4ABT and not on the other LN samples. Although substrate cut and other factors including intrinsic and impurity defects can affect surface chemistry and the amount of photogenerated charge and the size and distribution of metal nanoparticles, , it is clear from this work that photodeposition occurs and therefore photoexcited charge is present, on all substrates investigated, regardless of the cut. Thus, the orientation of the LN substrate does not appear to play the dominant role in the PIERS effect.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Given also that charge transfer from LN to Ag or 4ABT is permitted under UV irradiation, this raises the question as to why sustained PIERS is observed on x -cut LNOI–Ag–4ABT and not on the other LN samples. Although substrate cut and other factors including intrinsic and impurity defects can affect surface chemistry and the amount of photogenerated charge and the size and distribution of metal nanoparticles, , it is clear from this work that photodeposition occurs and therefore photoexcited charge is present, on all substrates investigated, regardless of the cut. Thus, the orientation of the LN substrate does not appear to play the dominant role in the PIERS effect.…”
Section: Resultsmentioning
confidence: 74%
“…During Raman laser excitation, electrons from defect states were reported to be promoted to the conduction band and transferred to the metallic nanoparticles . Previous studies of LN-based substrates have shown that UV light influences domain engineering, deposition of metallic nanoparticles, and the wettability of LN . Despite this progress, little is known about the influence of UV irradiation on Raman scattering from LN-based templates.…”
Section: Introductionmentioning
confidence: 99%